Dynamic Transcriptome Reveals the Mechanism of Liver Injury Caused by DHAV-3 Infection in Pekin Duck - Cao, Junting; Zhang, Yunsheng; Chen, Ying; Liang, Suyun; Liu, Dapeng; Fan, Wenlei; Xu, Yaxi; Liu, Hehe; Zhou, Zhengkui; Liu, Xiaolin; Hou, Shuisheng (Frontiers in Immunology, 2020)
Duck hepatitis A virus 3 (DHAV-3) is a wild endemic virus, which seriously endangers the duck industry in China. The present study aims to elucidate the mechanism of duck resistance to DHAV-3 infection. Both resistant and susceptible ducks were challenged with DHAV-3, and the dynamics of liver histopathological features and transcriptome were analyzed at 6, 12, 15, and 24 h post-infection (hpi). The histopathological features and serum biochemical indices (ALT and AST) were analyzed to estimate the status of liver injury. The result showed that the liver injury in susceptible ducks was more serious compared to that in the resistant ducks throughout the four time points. A total of 2,127 differentially expressed genes (DEGs) were identified by comparing the transcriptome of the two populations. The expression levels of genes involved in innate immune response increased rapidly in susceptible ducks from 12 hpi. Similarly, the expression of genes involved in cytokine regulation also increased at the same time points, while the expression levels of these genes in resistant ducks remained similar between the various time points. KEGG enrichment analysis of the DEGs revealed that the genes involved in cytokine regulation and apoptosis were highly expressed in susceptible ducks than in resistant ducks, which suggests that excessive cytokine storm and apoptosis may partially explain the mechanism of liver injury caused by DHAV-3 infection. Besides, we found that the FUT9 gene may contribute to resistance towards DHAV-3 in resistant ducklings. These findings will provide insight into duck resistance and susceptibility to DHAV-3 infection in the early phases, facilitate the development of a strategy for DHAV-3 prevention and treatment, and enhance genetic resistance via genetic selection in animal breeding.